(untitled) - Gosselin, Don (Australia, 2004)
Text offers students a complete introduction to the JavaScript language. Includes new exercises and projects; material has been updated to conform to XHTML standards. Designed for an introductory course in JavaScript.
Keywords: Javascript (computer program language)